The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.1172/jci116943
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotropin stimulates ovarian renin-angiotensin system in the rabbit.

Abstract: The present study was undertaken to assess the role of ovarian renin-angiotensin system (RAS) in the preovulatory cascade induced by gonadotropin exposure. In the in vitro perfused rabbit ovaries, exposure to human chorionic gonadotropin (hCG) enhanced the secretion rate of angiotensin II (Ang II) within 1 h. The secretion rate reached maximal levels at 6 h and then declined thereafter. The intrafollicular Ang II content and renin-like activity were also significantly increased at 2 and 4 h after exposure to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 50 publications
3
36
0
1
Order By: Relevance
“…We demonstrated previously a direct effect of Ang II on the rabbit ovary, suggesting that Ang II may play a critical role in the ovulatory cascade (7,20,30). The addition of saralasin, a peptide Ang II antagonist, to the perfusate blocked hCG-induced ovulation in vitro in a dose-dependent manner (20).…”
Section: Discussionmentioning
confidence: 86%
“…We demonstrated previously a direct effect of Ang II on the rabbit ovary, suggesting that Ang II may play a critical role in the ovulatory cascade (7,20,30). The addition of saralasin, a peptide Ang II antagonist, to the perfusate blocked hCG-induced ovulation in vitro in a dose-dependent manner (20).…”
Section: Discussionmentioning
confidence: 86%
“…The evidence that supports the existence of an ovarian RAS includes the following: i) the concentrations of Ang II in the follicular fluid were found to be higher than those in the plasma after human chorionic gonadotropin (hCG) treatment (Husain et al 1987), ii) high follicular fluid levels of Ang II were found after bilateral nephrectomy (Husain et al 1987), and iii) in vitro-perfused rabbit ovaries produced Ang II when exposed to hCG (Yoshimura et al 1994). However, renin is produced exclusively by kidneys and disappears from the plasma after bilateral nephrectomy (Do et al 1987).…”
Section: Ovarian Rasmentioning
confidence: 99%
“…(Rodland et al, 1992 (Werb and Burleigh, 1974) and rat uterus (Woessner and Ryan, 1973 (Zhu and Woessner, 1991) or from compartmentalization of the enzyme to the apex and the inhibitors to different compartments such as the granulosa cell layer (Mann et al, 1991 (Wan et al, 1996), or that there are divergent effects of calcium depending upon the intracellular concentration as previously reported for inositol phosphate (Bezprozvanny et al, 1991). (Pucell et al, 1987(Pucell et al, , 1991 (Kuo et al, 1991;Yoshimura et al, 1992Yoshimura et al, , 1994Yoshimura et al, , 1996bPeterson et al, 1993a). In loto, these findings suggest that All plays a role in follicular rupture.…”
Section: Introductionmentioning
confidence: 55%
“…Similarly, administration of captopril to perfused rabbit ovaries had no effect on ovulatory efficiency (Yoshimura et al, 1994 (Erickson, 1983) …”
Section: Introductionmentioning
confidence: 97%